Autologous Serum and Recombinant Nerve Growth Factor in the Complex Treatment of Neurotrophic Keratitis - E. A. Kasparova; Z. V. Surnina; N. R. Marchenko; L. S. Pateyuk; V. D. Yartsev (Oftalʹmologiâ, 2024)
Neurotrophic keratitis is a frequent complication of neurosurgical interventions caused by a loss of corneal sensitivity due to damage of the trigeminal nerve pathway. The article presents a clinical case of a successful treatment of a neurotrophic corneal ulcer developed after removal of a giant trigeminal neurinoma. Treatment with autologous serum instillations made it possible to achieve ulcer healing and unstable corneal epithelialization. Stable epithelialization was achieved after temporary replacement of the autologous serum topical application with recombinant human nerve growth factor. In addition to ulcer healing and complete corneal epithelialization, regeneration of nerve fibers was noted (according to cornea confocal microscopy data).